Public health priority setting on a national scale: The Scottish experience - C. Sumpter; M. Bain; G. McCartney; A. Blair; D. Stockton; J.W. Frank (Elsevier, 2023)
Objectives: Scotland has the lowest life expectancy in Western Europe and significant health inequalities. A national review of public health in 2015 found that there was a lack of coherent action across organisational boundaries, inhibiting progress. This paper describes a rapid (four-month) systematic approach to prioritisation of Scotland's public health challenges, which was evidence-based, transparent and made use of significant stakeholder engagement. Study design: Cross-sectional survey of stakeholders in deliberative meetings. Methods: An independent Expert Advisory Group (EAG) was formed to develop a typology of public health priorities, a long-list of potential priorities and ranking criteria. Deliberative stakeholder events were held at which the criteria were refined and priorities scored by participants from a wide range of stakeholder organisations. Results: The proposed typology identified three types of public health priorities: risk factors, social factors and system factors; medically defined disease entities were not used deliberately, to facilitate broad stakeholder participation. Fifteen criteria were identified to help identify priority issues, based on the scope of their burden, amenability to change, and multi-stakeholder preferences. Six public health priorities were selected by the EAG based on stakeholder scoring of a long-list against these criteria. Conclusion: Prioritisation is important in modern public health but it is challenging due to limited data availability, lack of agreed evidence on effectiveness and efficiency of interventions, and divergent stakeholder views. The Scottish experience nevertheless shows that useful public health priorities can be agreed upon by a wide range of stakeholders through a transparent, participatory and logical process.